Community Capital and Economic Returns of Koh Yao Noi Community Based Tourism, Phang Nga Province: ทุนของชุมชนและผลตอบแทนทางเศรษฐกิจของการท่องเที่ยวโดยชุมชน เกาะยาวน้อย จังหวัดพังงา - Untong, Akarapong; Phaokrueng, Ariya (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ บทความนี้มีวัตถุประสงค์เพื่อศึกษาทุนที่ชุมชนใช้พัฒนาการท่องเที่ยวและประเมินผลตอบแทนทางเศรษฐกิจของกิจกรรมที่เกี่ยวข้องกับการท่องเที่ยวโดยชุมชนเกาะยาวน้อย โดยประยุกต์แนวทางวิจัยเชิงคุณภาพในการเก็บ และตรวจสอบความน่าเชื่อถือและถูกต้องของข้อมูลจากการสัมภาษณ์เชิงลึกแกนนำชุมชน ก่อนประยุกต์ใช้ การวิเคราะห์แก่นสารและเชิงเนื้อหาเพื่อศึกษาทุนของชุมชนและการสะสมเพิ่มพูนทุนทางสังคมที่ชุมชนใช้พัฒนา การท่องเที่ยว รวมถึงการใช้การวิเคราะห์ต้นทุน-ผลตอบแทนเพื่อศึกษาผลตอบแทนทางเศรษฐกิจของกิจกรรม ที่เกี่ยวข้องกับการท่องเที่ยวโดยชุมชนเกาะยาวน้อย ผลการศึกษาพบว่า ทุนทางธรรมชาติที่โดดเด่น ทุนทางสังคมที่เข้มแข็ง และการหนุนเสริมจากรางวัลที่ได้รับต่างเป็นปัจจัยสำคัญที่ขับเคลื่อนการท่องเที่ยวโดยชุมชนเกาะยาวน้อยซึ่งมีการบริหารผ่านองค์กรชุมชนที่ไม่เป็นทางการแบบกระจายอำนาจและมีธรรมาภิบาลบนพื้นฐานการมีส่วนร่วมของคนในชุมชนตั้งแต่การวางนโยบาย การดำเนินงานจนถึงการได้รับผลประโยชน์ ผลจากการวิเคราะห์ต้นทุน-ผลตอบแทนแสดงให้เห็นว่ากิจกรรมที่เกี่ยวข้องกับการท่องเที่ยวส่วนใหญ่มีสัดส่วนต้นทุนการดำเนินงานสูง (มีค่าแรงงานเป็นต้นทุนสำคัญ) ในขณะที่ผลตอบแทนสุทธิที่ผู้ให้บริการได้รับมาจากค่าจ้างแรงงาน (ผู้ให้บริการดำเนินการเอง) และผลตอบแทนสุทธิ โดยทุกกิจกรรมมีสัดส่วนผลตอบแทนเหนือต้นทุนการดำเนินงานบวกกับค่าแรงและมีสัดส่วนมากกว่าครึ่งหนึ่งของรายรับ ดังนั้นหากกิจกรรมที่เกี่ยวข้องกับการท่องเที่ยวมิใช่อาชีพหลักที่ลงทุนใหม่ ชาวบ้านจะยังคงได้รับผลตอบแทนทางเศรษฐกิจที่คุ้มกับการลงทุนในกิจกรรมนั้นๆ จากผลการศึกษามีข้อเสนอแนะที่สำคัญคือ การพัฒนาการท่องเที่ยวโดยชุมชนควรเริ่มภายในชุมชนบนพื้นฐานการมีส่วนร่วมตั้งแต่การสำรวจทุนที่ใช้ในการพัฒนา การดำเนินการและการจัดการ จนถึงการกระจายผลประโยชน์ เพื่อให้เกิดการสะสมเพิ่มพูนทุนทางสังคมอย่างต่อเนื่อง ส่งเสริมกิจกรรมที่ลงทุนไม่มากและใช้แรงงานส่วนเกิน เพื่อให้ชุมชนได้รับผลตอบแทนที่คุ้มค่าและนำมาสู่การพัฒนาการท่องเที่ยวที่ยั่งยืนโดยชุมชน ABSTRACT This article aims to study the community capital used to develop tourism and to evaluate the economic returns of each activity related to Koh Yao Noi community-based tourism (CBT). The qualitative research guideline was applied to collect and check the reliability and accuracy of the data obtained from the in-depth interviews with community leaders before applying the thematic analysis and content analysis to study the community capital and social capital accumulation that are used there to develop tourism. Additionally, cost-benefit analysis was used to evaluate the economic benefits of the activities related to tourism by the Koh Yao Noi community. The results revealed that outstanding natural capital, strong social capital, and supplementary support from the awards are the main driving factors of Koh Yao Noi CBT. This CBT is organized by an informal community organization, which has decentralized management and good governance based on the participation of the community in terms of planning, operating and receiving benefits. The results from the cost-benefit analysis showed that most activities related to tourism have a high proportion of operating costs (mainly labor costs). On the other hand, the net benefit that the owners receive come from two main elements: wages (the owners operated by themselves) and net benefits. In addition, all activities have a return ratio above operating costs, plus wages, and account for more than half of the revenue. Therefore, if tourism-related activities are not the main occupation for new investment, the villagers will still receive economic returns that are worth the investment in that activity. According to the study, the significant suggestions are whether community-based tourism development should begin from the community through the participation in exploring the funding sources for development, operating, and management, including the distribution of benefits. That is in order to continuously accumulate and increase social capital as well as to promote activities that do not require the investment of a lot money or use excess labor in order to receive worthwhile returns and to contribute to sustainable tourism development by communities.